Transformasi Potensi Lokal Menjadi Komoditas Unggulan Melalui Pendekatan Asset Based Community Development Pada Produk Kopi Ragasakti Setianegara Kuningan - Saehu Abas; Dede Abdurohman; Hajjin Mabrur; Zulfi Amaluddin; Khamdiallah; Amatullah Azizah (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
Ragasakti Coffee from Setianegara Village represents a local commodity with strategic value for asset-based community development. This study aims to analyze community asset potential and participation, the transformation of local potential and external support, as well as the socio-economic impacts and future expectations in the development of Ragasakti Coffee. A qualitative approach with the Asset Based Community Development (ABCD) framework was employed to explore community assets participatively and to facilitate the transformation of local potential into a leading commodity. Data were collected through in-depth interviews with village officials, coffee farmers, and practitioners; participatory observation; and document studies. Data analysis applied Miles and Huberman’s model, including data reduction, data display, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings reveal that Ragasakti Coffee possesses significant assets, including fertile land, farming skills, and social capital rooted in mutual cooperation and cultural identity. Community participation is high across the entire production chain, while transformation occurs through the integration of traditional practices with youth innovation. External support from government, universities, and the private sector strengthens development through training, technology, and promotion. Socio-economic impacts include increased household income, new business opportunities, stronger social cohesion, and greater youth involvement. The study also highlights a collective aspiration for Ragasakti Coffee to penetrate national and international markets and to serve as the basis for coffee-based tourism. In conclusion, Ragasakti Coffee functions not only as a driver of local economic growth but also as a symbol of socio-cultural identity, requiring strong community institutions and multi-stakeholder collaboration to ensure sustainability.